Economic and non-economic loss and damage to climate change: evidence from a developing country shrimp farms to cyclone Bulbul - Md. Monirul Islam (Fisheries and Aquatic Sciences, 2022)
Loss and damage have become a vital contemporary issue in climate change studies and actions in developing countries. However, studies are scant on this in the fisheries sector around the world. In Bangladesh, there is no study on the loss and damage in fisheries dependent communities. This study assesses economic and non-economic loss and damage to coastal shrimp farms due to cyclone Bulbul in Gabura Union of Shyamnagar Upazila, Satkhira district, using a mixed method approach. Results show that all shrimp farms’ dependent communities are affected by cyclone Bulbul to some extent. About 14%, 57%, and 29% of the farms were totally, heavily and moderately damaged due to farm inundation and dyke damage. The estimated mean loss and damage per shrimp farm was worth USD 4,633. Around 31% and 72% of the farms’ fencing nets and traps were lost, which was worth USD 333 per farm. There were also loss and damage to other resources such as houses, solar panels, livestock and agricultural crops where the estimated mean loss and damage per household was worth USD 3,170. This study reported that the rich shrimp farmers encountered proportionately more economic loss and damage than their poor counterparts. However, this does not mean that the poor suffered less. The current study found a range of non-economic loss and damage in different aspects of the shrimp farmers’ household members such as unbearable mental pain, deterioration of health, physical injuries, disabilities, etc. and access to services (e.g., inadequate food, lack of safe drinking water, lack of medical facilities, disruption of education systems), social infrastructure (e.g., damage of roads and markets) and disturbance of cultural functions. The findings suggest that urgent short- and long-term actions may be taken to save the aquaculture farms and dependent livelihoods from economic and non-economic loss and damage to cyclones in future.